PENGARUH FAKTOR MODAL DAN PEMBINAAN MANAJEMEN TERHADAP KINERJA KOPERASI DI KOTA PEKANBARU - Multisari Fatra Multisari Fatra; Caska '; Gani Haryana Gani Haryana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : This research aims to know about the effect of capital source and management guidance towards cooperative performance in Pekanbaru. The method of this research using quantitative-descriptive reasearch method. The population has amount of 830 cooperations and 89 samples of cooperation. Data collection instrument is enquette with Likert scale for independent variable : Capital Factor (X1) and Management Guidance (X2), for dependent variable using document : Cooperative Performance (Y). Data Analysis Technique is statistic which is used by doubled-linear regression. From the result, is to conclude that : (1) capital resource and management performance effects the cooperative management performance in Pekanbaru; (2) The effect factors of capital leverage and management guidance towards cooperation’s management performance in the amount of 50,8% in Pekanbar;. (3) The measurement of cooperation’s performance in Pekanbaru using Development Ladder Assessment (DLA) has yellow zone criteria which means it has been satisfied and still needing the follow-up action to improve cooperation’s performance mainly to the cooperation’s resources.Keywords : Capital Resource, Management Guidance, Cooperative Performance.